CD4+CD25highCD127low regulatory T cells in peripheral blood are not an independent factor for chronic graft-versus-host disease after allogeneic stem cell transplantation - Dengler, Jolanta; Dehghani Barengi, Selma; Schönland, Stefan; Hegenbart, Ute; Ho, Anthony Dick; Dreger, Peter (The ScientificWorld journal, 2012)
Background. The therapeutic efficacy of allogeneic hemopoietic stem cell transplantation (HSCT) largely relies on the graft-versus-leukemia (GVL) effect. Uncontrolled graft-versus-host disease (GVHD) is a feared complication of HSCT. Regulatory T cells (Treg) are a subset of CD4